2022
DOI: 10.1155/2022/6683104
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Microenvironment-Induced Reduction in PTEN-L Secretion Promotes Non-Small Cell Lung Cancer Metastasis through PI3K/AKT Pathway

Abstract: Objective. Lung cancer is the leading cause of cancer-related deaths worldwide. The aim of this study was to investigate the effects of hypoxic microenvironment on PTEN-L secretion and the effects of PTEN-L on the metastasis of non-small cell lung cancer (NSCLC) and the potential mechanisms. Methods. The expression levels of PTEN-L in NSCLC tissues, cells, and cell culture media were detected. The transfection of PTEN-L overexpression construct or HIF-1α-siRNAs was conducted to manipulate the expression of PTE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…In addition, this study also confirmed that PTEN expression was elevated in rats with Achilles tendinopathy. PTEN is a prominent tumor suppressor gene [ 47 ] that inhibits the PI3K/AKT pathway through lipid phosphatase activity [ 48 , 49 ]. Recently, PTEN has been revealed to be involved in tendon healing and regeneration [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this study also confirmed that PTEN expression was elevated in rats with Achilles tendinopathy. PTEN is a prominent tumor suppressor gene [ 47 ] that inhibits the PI3K/AKT pathway through lipid phosphatase activity [ 48 , 49 ]. Recently, PTEN has been revealed to be involved in tendon healing and regeneration [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, HIF-1α expression can be regulated by the PI3K/AKT/mTOR signaling pathway, fumarate hydratase (FH), succinate dehydrogenase (SDH), phosphatase and tensin homolog (PTEN), protein kinase A (PKA), and Ra4/MAPK pathway under hypoxic conditions or independently of oxygen concentrations due to mutations of any of these components, [67][68][69][70].…”
Section: The Hypoxic Inducible Factors (Hifs)mentioning
confidence: 99%